Three keys eaudiobook - Yang, Kelly (Front Desk, 2020)
The story of Mia and her family and friends at the Calivista Motel continues in this powerful, hilarious, and resonant sequel to the award-winning novel Front Desk . Mia Tang thinks she's going to have the best year ever. She and her parents are the proud owners of the Calivista Motel, Mia gets to run the front desk with her best friend, Lupe, and she's finally getting somewhere with her writing!But as it turns out, sixth grade is no picnic...1. Mia's new teacher doesn't think her writing is all that great. And her entire class finds out she lives and works in a motel! 2. The motel is struggling, and Mia has to answer to the Calivista's many, many worried investors.3. A new immigration law is looming and if it passes, it will threaten everything — and everyone — in Mia's life.It's a roller coaster of challenges, and Mia needs all of her determination to hang on tight. But if anyone can find the key to getting through turbulent times, it's Mia Tang!